(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2010)
An experiment was conducted in order to evaluate the effect of different fertilizer regimes on biological productivity and water quality of limed acid sulfate soils fishponds. The experiment consisted of 4 different fertilizer treatments i.e., control without fertilizer input, chicken manure 50 g/m 2 /week, chicken manure 75 g/ m 2 /week, and inorganic fertilizer (6 g of urea + 3.5 g of TSP /m /week), each treatment with 3 replications. Result of experiment shows that Inorganic fertilization gave the highest chlorophyll a concentrations (83.40 mg/m 3 ), and the highest net fish yields 7.53 kg /ha /day), but had a lower water pH than that in control. Ponds which are fertilized with chicken manure 75 g /m2 /week gave the highest fish survival rate (100%) while in ponds without fertilizer inputs only 3.3 % of stocked fish was survived.